Bevacizumab combined with apatinib enhances antitumor and anti-angiogenesis effects in a lung cancer model in vitro and in vivo. (20th October 2020) - Wang, Mingting; Zeng, Qin; Li, Yuan; Imani, Saber; Xie, Danna; Li, Yinghua; Han, Yunwei; Fan, Juan
Abstract: Angiogenesis is involved in the proliferation and metastasis of solid tumours; hence, it is an attractive therapeutic target. However, most patients who undergo anti-angiogenic drug treatment do not achieve complete tumour regression, resulting in drug resistance. The objective of this research is to explore the therapeutic effect of combining bevacizumab (Bev), an anti-vascular endothelial growth factor (VEGF)-A antibody, with apatinib (Apa), a VEGR receptor (VEGFR)-2-targeting tyrosine kinase inhibitor, in non-small cell lung cancer (NSCLC). In vitro, we assessed the influence which Bev + Apa treatment exerts upon the proliferation as well as apoptosis of Lewis lung carcinoma (LLC) cells in virtue of the 3-(4, 5-dimethyl-thiazol-2-yl)-2, 5-diphenyltetrazolium bromide as assay as well as Annexin V staining, respectively. For in vivo assessment, we established a tumour-bearing mouse model with LLC cells and investigated the anti-angiogenic and antitumor effects of Bev + Apa by 18 F-FDG PET/CT imaging, immunohistochemistry and TUNEL staining. Bev + Apa treatment significantly inhibited LLC cell growth and proliferation in a larger scale compared to therapy of either of the only agent. Bev + Apa inhibited tumour growth and extended the median survival time of tumour-bearing mice. Mechanistically, Bev + Apa reduced angiogenesis by inhibiting VEGF and VEGFR-2 expression and reducing glucose metabolism in tumour tissues. Thus, Bev and Apa inhibited tumour angiogenesis synergistically, indicating their potential clinical utility for NSCLC treatment.